Improving Security and Economic Opportunity Through Indonesia-Japan Maritime Cooperation Year 2016-2021 - Sari, Suwarti; Auliya, Putri (UIN Sunan Gunung Djati, 2026)
This study will analyze the Indonesia-Japan maritime cooperation in the construction of the Patimban Port. This cooperation, which is considered very important to support the progress of Indonesia's national port sector, also supports efforts to guarantee the security of Indonesia's maritime areas. The cooperation in the infrastructure sector between Indonesia and Japan through the Japan International Cooperation Agency (JICA) is building the Patimban Port in Subang, West Java, so that it can later become infrastructure supporting the consolidation of Indonesian ports, as is the case with the Tanjung Priok Main Port. This is to answer the problems faced by Indonesian ports, which in terms of infrastructure are still not ready and not sufficient to accommodate cargo related to the demands for the development of the growth of the flow of goods and services through sea ports which continues to increase. With the existence of the Indonesia-Japan project in the Patimban Port, it is hoped that it will support the national port system that can be well consolidated, as a unified sea freight shipping flow that can support each other to expedite the delivery of goods effectively and efficiently. So, with the existing progress, it will not only support the improvement of the quality of national ports and improve the economy. But is also realizing maritime security that is more well-managed by looking at the prospect of ports as an important sector in Indonesia's capability as a maritime country.